Design of Flood Early Warning Monitoring System Using a Microcontroller Ultrasonic Sensor Based on Website and Telegram Chat Bot (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
Floods are devastating natural disasters that frequently occur in Indonesia, particularly during the rainy season. The losses incurred by this disaster are significant, as it happened suddenly, leaving little time to evacuate valuables or move to a safer location. The financial and material losses, as well as the loss of lives, are overwhelming, as there is no early warning system in place to minimize the damage. However, a solution may exist in the form of an early warning system that uses ultrasonic sensors and microcontrollers to gauge water levels and alert the public of impending danger. To this end, we have developed a flood early warning monitoring system that utilizes the HC-SR04 ultrasonic sensor as a water level meter and the ESP32 microcontroller as an automatic early warning controller that sends alerts via telegram and sounds an alarm when river water levels reach the surface. Additionally, the flood alert website displays the water level value for added convenience. To create this system, we utilized several tools, including the ESP32, HC-SR04 ultrasonic sensor, jumper cables, buzzer, and Arduino IDE. The end goal is a flood early warning monitoring tool that provides peace of mind to those who are frequently affected by floods, reducing material losses and even fatalities